The Effect Of Project Based Learning Model Based STEM On The Knowledge Competence Of Class VII Students Of SMPN 8 Payakumbuh - Kurnia, Irma; Lestari, Tuti (Universe, 2025)
The low competence of knowledge can arise due to factors that influence learning, namely the method factors used during the learning process in class, the use of learning models that are less varied, and the enthusiasm of students in learning is still low. One learning model that can be tried to be applied to overcome this problem is the STEM-based Project-based learning model. This research is a type of quasy experiment research that aims to determine the effect of the application of STEM-based project-based learning models on the knowledge competence of class VII students of SMPN 8 Payakumbuh. The research design used was a non equivalent control group design. In the experimental class, STEM-based Project Based Learning was applied, while in the control class, conventional learning was applied. The results of hypothesis testing based on the data obtained in the posttest data research, namely H1 is accepted and H0 is rejected, it can be interpreted that there is a significant average difference in the learning outcomes of students in the experimental class and the control class. So that there is an influence of the project based learning learning model on the knowledge competence of students